Dry matter yield and nutrient uptake in corn plants as a function of potassic fertilization and of basis soil saturation - Andreotti, Marcelo; de Souza, Euclides Caxambu Alexandrino; Crusciol, Carlos Alexandre Costa; Rodrigues, João Domingos; Bull, Leonardo Theodoro (Pesquisa Agropecuaria Brasileira, 2000)
The purpose of this research was to study dry matter yield and nutrients uptake by corn plants as a function of potassic fertilization and of soil basis saturation. An experiment was conducted under greenhouse conditions, using an early single hybrid corn Zêneca 8392 grown in 30 L pots, tested with three types of soil (Quartzpsamment and two alic Dark-Red Latosol - Haplorthox), with two levels of basis saturation (40 and 70 %) and four levels of potassium content (0.5, 1.5, 3.0 and 6.0 mmolc dm-3). A completely random design with four replications was utilized. The basis saturation treatments were calibrated by liming the soils with a mixture of 4:1 of calcium and magnesium carbonate, according to soil type. K content in the soil was established by applying 0, 3.62, 7.24 and 14.48 g of KCl per 30 L pot. P (200 mg kg-1) and Zn (5 mg kg-1) were applied to all treatments at sowing time. N was applied at sowing time (83.7 mg kg-1) as well as at top dressing, 25 and 40 days after seedling emergence, totalizing 200 mg kg-1. Sixty days after seedling emergence the dry matter weight and N, P, K, Ca and Mg content of the leaves and stems were determined. The dry matter yield was increased by K concentrations in the soil up to 1.5 mmolc dm-3. The increase in soil K levels allowed decrease on the Ca and Mg concentrations in corn dry matter. The increase of basis saturation and soil Ca and Mg levels decrease corn plant K uptake.
Keywords: Zea mays; liming; plant nutrition; soil texture